2013
DOI: 10.1177/1708538113516445
|View full text |Cite
|
Sign up to set email alerts
|

Application of endovascular stent placement as a remedy for spontaneous isolated superior mesenteric artery dissection

Abstract: Endovascular stent placement is a simple and safe alternative to aggressive surgery or uncertain observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…7,16 This obliteration of the side branches does not occur with the use of bare stents alone or stent assisted coiling, and so these techniques are widely used in the management of IMAD. 7,15,17 Previous studies of endovascular therapy have demonstrated a high technical success rate for both bare stents alone and stent assisted coiling; 7,8,15,17,18 although this study demonstrated similar results, the numbers are small and there is a risk of a type II statistical error. Studies with larger sample sizes are needed to validate the findings.…”
Section: Discussionsupporting
confidence: 50%
“…7,16 This obliteration of the side branches does not occur with the use of bare stents alone or stent assisted coiling, and so these techniques are widely used in the management of IMAD. 7,15,17 Previous studies of endovascular therapy have demonstrated a high technical success rate for both bare stents alone and stent assisted coiling; 7,8,15,17,18 although this study demonstrated similar results, the numbers are small and there is a risk of a type II statistical error. Studies with larger sample sizes are needed to validate the findings.…”
Section: Discussionsupporting
confidence: 50%
“…[1][2][3][4][5][6][7] Patients with ISMAD are at a high risk of suffering both the rupture of the dissection, and symptoms of mesenteric ischemia. [1][2][3][4][5][6][7][10][11][12] Since it is a rare condition, the exact risk factors, its incidence rate and natural course of disease progression, and optimal treatment strategies are still not definitively established. The first-line treatment for ISMAD is typically a conservative approach, which has been used in the majority of previous reports where it has been reported to be successful in 12.5% to 70.6% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…5,[16][17][18] Twenty-two patients (18.1%) underwent this treatment option in whom the symptomatology was resolved at the end of follow-up period. Pharmaceutical treatment was mentioned in five studies 5,13,16,18,19 with 21 (17.3%) patients. Out of 21 patients, anticoagulants using low molecular weight heparin (LMWH) were used in 11 patients (52.3%), while antiplatelet agents in 6 (28.5%) patients.…”
Section: Asymptomatic Patientsmentioning
confidence: 99%
“…Less applicable diagnostic modalities included ultrasonography 18 and the magnetic resonance angiography (MRA) 20,36 while digital subtraction angiography (DSA) was performed only in four studies. 20,22,28,29 The imaging classification system of the SISMAD proposed by Sakamoto et al 6 was used by 14 studies, 6,16,18,19,21,[23][24][25]27,29,31,32,35,37 the modified by Yun classification, 8 was used by four studies, 15,22,26,28 while two studies 5,34 did not report the classification system used. The total number of stents used for endovascular treatment of SISMAD among the eligible studies was 86.…”
Section: Conservative Treatmentmentioning
confidence: 99%